Effect of Certain Salts and their Interaction on Germination and Seedling Development of Barrel Medic Seeds - Al-Jibury, L K; Al-Charchafchi, F; Jawad, M S (Annals of Arid Zone, 2016)
Inhibitory effects of various levels of sodium chloride, magnesium chloride, potassium sulfate (singly and in combination) and mannitol at equal osmotic pressures on germination and seedling development of Barrel medic seeds ,Medicago truncatula L.) were studied, The reductions in germination and total seedling length were, in general, greater by salts. particularly at higher osmotic pressure, than by mannitol. At equal osmotic pressures, potassium sulfate and magnesium chloride reduced germination and total seedling length more than sodium chloride. On the basis of recovery of ungerminated seeds from the single salt treatments with equal osmotic concentrations, magnesium chloride was the most toxic. When the chlorides of sodium and magnesium were combined with potassium sulfate, the inhibitory effect of single salt was eliminated and a sort of synergistic action was developed.